An integrated approach to fetal growth restriction. (January 2017) - Figueras, Francesc; Gratacos, Eduard
Abstract : Fetal growth restriction (FGR) is among the most common complications of pregnancy. FGR is associated with placental insufficiency and poor perinatal outcomes. Clinical management is challenging because of variability in clinical presentation. Fetal smallness (estimated fetal weight <10th centile for gestational age) remains the best clinical surrogate for FGR. However, it is commonly accepted that not all forms of fetal smallness represent true FGR. In a significant subset of small fetuses, there is no evidence of placental involvement, perinatal outcomes are nearly normal, and they are clinically referred to as "only" small for gestational age (SGA). Doppler may improve the clinical management of FGR; however, the need to use several parameters sometimes results in a number of combinations that may render interpretation challenging when translating into clinical decisions. We propose that the management of FGR can be simplified using a sequential approach based on three steps: (1) identification of the "small fetus, " (2) differentiation between FGR and SGA, and (3) timing of delivery according to a protocol based on stages of fetal deterioration. Highlights: Management of FGR is challenging because not all small fetuses are true forms of growth restriction and clinical presentation is variable. Doppler is the central tool for management, but there are multiple parameters and combinations involved. We propose a stage-based approach to identify small fetuses, distinguish FGR from SGA, and plan follow-up intervals and timing of delivery.